Characterization of Edwardsiella piscicida CK108 flagellin genes and evaluation of their potential as vaccine targets in the zebrafish model. Issue 2 (29th November 2021) - Choe, Yunjeong; Lee, Donghee; Seong, Minji; Yoon, Ju Bin; Yang, Jun Hyeok; Yang, Jin‐Young; Moon, Ki Hwan; Kang, Ho Young
Abstract: The control of bacterial pathogens, including Edwardsiella piscicida, in the aquaculture industry has high economic importance. This study aimed to identify a potential live vaccine candidate against E. piscicida infection to minimize the side effects and elicit immunity in the host. This study evaluated the virulence factors of E. piscicida CK108, with a special focus on the flagella. E. piscicida has two important homologous flagellin genes, namely flagellin‐associated protein ( fap ) and flagellin domain‐containing protein ( fdp ). CK226 (Δ fap ), CK247 (Δ fdp ) and CK248 (Δ fap, fdp ) mutant strains were constructed. Both CK226 and CK247 displayed decreased length and thickness of flagellar filaments, resulting in reduced bacterial swimming motility, while CK248 was non‐motile as it lacked flagella. The loss of flagella and decreased motility was expected to decrease the pathogenicity of CK248. However, the median lethal dose (LD50 ) of CK248 against zebrafish was lower than those of the wild‐type, CK226 and CK247 strains. The protective immunity and cytokine gene expression levels in the CK248‐infected zebrafish were lower than those in the wild type‐infected zebrafish. In conclusion, Fap and Fdp are essential for flagella formation and motility, and for stimulating fish immune response, which can be utilized as a potential adjuvants for E. piscicida vaccination.